Climate change impacts and effects on health system: A challenge towards achievement of Sustainable Development Goal 3 in South Africa - Tirivangasi, Happy Mathew; Rankoana, Sejabaledi Agnes; Nyahunda, Louis (Technium Social Sciences Journal, 2021)
The aim of this paper is to present climate change health related effects that may pose a challenge for South Africa to attain South Africa’s plans to achieve Sustainable Development Goal (SGD) 3. It examined South Africa’s preparedness to address the impacts of climate change in order to best achieve SDGs 3. Climate change is a challenging phenomenon, which has seen many people around the world being affected by its effects unaware and unprepared. Climate change affects weather patterns, for instance rainfall patterns and temperatures. Consequently, this resulted in draughts, floods, diseases, veld fires, high temperatures, changing times of floods occurrences and depleted water resources in Africa and the rest of the world. This has placed human life in danger. Considering the increasing burden of diseases, the United Nations (UN) adopted Sustainable Development Goals (SDGs) to address of poverty, hunger disease and want by 2030. However, climate change threatens the ability of countries to achieve this by the anticipated time. The researchers conducted an extensive content analysis by interrogating various sources of literatures sources that include journal articles, thesis, academic books, and documents written by the government of South Africa. The study reveals that that climate related deaths will increase between 2030 and 2050 due to these health impacts of climate change. The study reveals that South Africa, like many other countries in Sub-Saharan Africa faces threat of vector borne diseases, mental health, malnutrition, and diarrheal, and other disease resulting from water scarcity and heat waves. This comes because of high prevalence of drought, floods, and increased temperatures. The study recommends early awareness and new communication strategies for the promotion of mental health, heat education campaign and prevention of vector borne diseases.